2011
DOI: 10.1016/j.ypmed.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and socioeconomic correlates of breakfast skipping in Hong Kong primary 4 schoolchildren

Abstract: Breakfast skipping was significantly related to various health-compromising lifestyle characteristics and lower parental education. Breakfast habit can be a potential lifestyle indicator. Education programmes aimed at specific target groups should encourage regular breakfast consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 19 publications
3
47
4
Order By: Relevance
“…Various studies have reported the prevalence of breakfast skipping, 2,12,23 but few have considered the prevalence by breakfast location. We found that 85.3% and 80.9% of children had breakfast at home in P4 and P6, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the prevalence of breakfast skipping, 2,12,23 but few have considered the prevalence by breakfast location. We found that 85.3% and 80.9% of children had breakfast at home in P4 and P6, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Briefly, SHS participants attended free annual appointments at 1 of 12 SHS centres located in different districts of Hong Kong. From primary 4 (P4; US grade 4), participants completed a biennial self-administered standardised health and lifestyle assessment questionnaire in Chinese.…”
Section: Study Samplementioning
confidence: 99%
“…just boys or just girls) (34,37) , and another found no relationship between the two (22) . All of these previous studies examined the breakfast skipping-PA relationship cross-sectionally (17,21,22,26,(34)(35)(36)(37) . While most used selfreported measures of PA (17,21,22,35,36) , a few have used objective measures (34,37) , and one used both self-reported and objective measures (26) .…”
mentioning
confidence: 99%
“…An association between skipping breakfast and poor-quality diets that influence the weight status of children has also been observed [47,48].…”
Section: Discussionmentioning
confidence: 95%
“…Skipping breakfast, in particular, has short-and longterm effects on children [46,47], and researchers have observed a tendency for this behavior to persist from childhood into adulthood, and was associated with a greater WC, higher fasting insulin, a higher BMI, and higher total cholesterol and LDL-cholesterol concentrations [9]. An association between skipping breakfast and poor-quality diets that influence the weight status of children has also been observed [47,48].…”
Section: Discussionmentioning
confidence: 99%